Logical Argument from Evil and Theism - Andrea Aguti (Religions, 2022)
The article argues that the logical argument from evil is dead, and the new version presented by James Sterba cannot resurrect it. In the first part, I say that the logical argument from evil is dead either because, in the version given by Mackie, it was successfully refuted by Plantinga and other theists or because, by inviting a reformulation of theistic doctrines, it was nevertheless superseded by contemporary versions of theism, such as open theism. In the second part, I argue that the two significant moves made by Sterba to resurrect the logical argument from evil fail in their intent either because the premise they start does not necessarily give rise to an atheistic conclusion or because the premise is unacceptable for the theist.